1970
DOI: 10.1111/j.2044-8279.1970.tb02100.x
|View full text |Cite
|
Sign up to set email alerts
|

The Concurrent Validity of Two Types of Spelling Test

Abstract: SUMMARY. Few tests of spelling attainment have been validated against the criterion of spelling accuracy in everyday writing, which, it is contended, is the prime objective of teaching spelling. An investigation is described comparing the spelling performance of 506 children (median age 11 : 6) in their written work and on dictated-word (recall) and multiple-choice (recognition) types of test. The dictated word test had a slightly higher concurrent validity, but other factors which should be taken into account… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

1982
1982
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 1 publication
1
3
0
2
Order By: Relevance
“…because they both required test-takers to spell out the words they heard. In addition, the sigriificant correlations arnong the four tests (i.e., story form, timed dictation, list form, and multiple-choice) were consistent with the results from the previous studies (e.g., Altred, 1984;Freyberg, 1970;Westwood, 1999;Takanami, 2012).…”
Section: Pearson's Correlations Between Vocabulary Size and Spelling supporting
confidence: 89%
See 1 more Smart Citation
“…because they both required test-takers to spell out the words they heard. In addition, the sigriificant correlations arnong the four tests (i.e., story form, timed dictation, list form, and multiple-choice) were consistent with the results from the previous studies (e.g., Altred, 1984;Freyberg, 1970;Westwood, 1999;Takanami, 2012).…”
Section: Pearson's Correlations Between Vocabulary Size and Spelling supporting
confidence: 89%
“…Among them, spelling knowledge is relevant to the form and the meaning of knowing a word. In general, receptive knowledge relates to listening and reading while productive knowledge relates to speaking and writing (e,g., Nation, 2001), However, in order to evaluate knowledge of English vocabulary, EFL educators in Japan need to consider the receptive direction as one from L2 (English) to Ll (Japanese) and the productive direction as one knowledge (e.g., Allred, 1984;Croft, 1982;Moore, 1937;Northby, 1936) while other studies fbcus on the relationships among spelling tests and other types of tests that measure learners' writing ability (e.g., Freyberg, 1970;Westwood, 1999), proficiency (e.g., Carpenter & Carpenter, 1978), or cognitive fbnctions (e.g., Allen & Ager,l965). In sum, research can focus on (a) spelling knowledge or (b) (e.g., multiple-choice).…”
Section: Receptive and Productiye Knowledge Of Vocabularymentioning
confidence: 99%
“…Studies from English-speaking countries have consistently reported high correlations between spelling skills and performance in proofreading tasks from elementary to secondary school (Allen & Ager, 1965;Allred, 1984;Croft, 1982;Freyberg, 1970;Frisbie & Cantor, 1995;Westwood, 1999). The two available studies from German-speaking countries, both of which focus on secondary-school children, yielded similar results (Lenhart et al, 2019;Schneider et al, 2014).…”
Section: Research Rationale and Hypothesesmentioning
confidence: 82%
“…A factor analysis by Allen and Ager (1965) found no difference between tasks measuring the active and passive component of spelling, that is, scores obtained in both tasks were highly correlated and loaded on a single factor. Freyberg (1970) compared three different spelling tasks (free writing, dictation, and error detection multiplechoice tests) for secondary-school students from New Zealand. Freyberg concluded that dictations (recall) and error detection (recognition) measured nearly the same competency given that the highest correlation was found between these two tasks.…”
Section: Measurement Of Spelling Competencies and Validity Of Edtsmentioning
confidence: 99%
“…Allen und Ager (1965) konnten zeigen, dass verschiede ne Maße der produktiven und rezeptiven Rechtschrei bung auf demselben Faktor luden und hoch miteinander korreliert waren. Freyberg (1970) verglich die Recht schreibleistungen von Schülerinnen und Schülern einer neuseeländischen Mittelschule in einem Diktat sowie in einem Fehleridentifikationstest mit den Leistungen in einer Probe ihres freien Schreibens. Er fand hohe Korre lationen zwischen beiden Variablen und der freien Ver schriftung, wobei die Leistung im Diktat leicht höher mit der Fehleranzahl im freien Schreiben korrelierte (r = .72) als die Leistung im Fehleridentifikationstest (r = .68).…”
Section: Fehleridentifikationstests Zur Erfassung Von Rechtschreibkompetenzenunclassified